Аspects of the mythical on the example of Рobert Мusil’s Kakanien - Valkova, Vladimira (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
After general theoretical reflections on the aesthetic and artistic dimensions of the mythical in modernism and in Musil, the article explores the myth of the multilingual and multicultural Kakanien in the novel The Man without Qualities. At the same time, it brings into focus such manifestations of the myth as illustrate its deconstruction in Musil: the mythologizing of the Habsburg state ideology, of the Kaiser, of the supranational cultural community and of the language policy of Austria-Hungary. The question of how myth and utopia relate to each other in Musil will be also discussed.
Keywords: Musil; Kakanien; myth; deconstruction; utopia